Significance of electrocardiographic Right Bundle Branch Block in trained athletes - Kim, J. H.; Noseworthy, P. A.; McCarty, D.; Yared, K.; Weiner, R.; Wang, F.; Wood, J.; Hutter, A. M.; Picard, M. H.; Baggish, A. L. (The American Journal of Cardiology, 2011)
We sought to determine the clinical and physiologic significance of electrocardiographic complete right bundle branch block (CRBBB) and incomplete right bundle branch block (IRBBB) in trained athletes. The 12-lead electrocardiographic and echocardiographic data from 510 competitive athletes were analyzed. Compared to the 51 age-, sport type-, and gender-matched athletes with normal 12-lead electrocardiographic QRS complex duration, the 44 athletes with IRBBB (9%) and 13 with CRBBB (3%) had larger right ventricular (RV) dimensions, as measured by the basal RV end-diastolic diameter (CRBBB 43 ± 3 mm, IRBBB 38 ± 6 mm, normal QRS complex 35 ± 4 mm, p <0.001) and RV end-diastolic area (CRBBB 33 ± 5, IRBBB 27 ± 7, and normal QRS complex 23 ± 3 cm2; p <0.001). Athletes with CRBBB also had a relative reduction in the RV systolic function at rest as assessed by the RV fractional area change and peak systolic tissue velocity. Finally, QRS prolongation was associated with parallel increases in interventricular dyssynchrony (basal RV to basal lateral left ventricular peak systolic tissue velocity time difference: CRBBB 112 ± 15, IRBBB 73 ± 33, normal QRS complex 43 ± 39 ms, p <0.001). Despite these findings, no athlete with CRBBB or IRBBB was found to have pathologic structural cardiac disease. In conclusion, among trained athletes, CRBBB and IRBBB appear to be markers of a structural and physiological cardiac remodeling triad characterized by RV dilation, a relative reduction in the RV systolic function at rest, and interventricular dyssynchrony.